Методологічні засади універсалізації національного права - Іванченко, Ольга Миколаївна; Иванченко, Ольга Николевна; Ivanchenko, Ol'ga (My University, 2013)
The article deals with the problems of universalization of national law in the context of globalization. The author analyzes the main means of this inclusive process: the internationalization of law, harmonization of law, law implementation, integration of law, law approximation, reception of law, adaptation of law. The author considers the use of such means in interaction of national and international law on the example of law of Ukraine.
Іванченко О. М. Методологічні засади універсалізації національного права / О. М. Іванченко // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 529-538.
Keywords: глобалізація; універсалізація національного права; засоби універсалізації права; інтернаціоналізація права; гармонізація права; імплементація права; інтеграція права; апроксимація права; рецепція права; адаптація права; глобализация; универсализация национального права; средства универсализации права; интернационализация права; гармонизация права; имплементация права; интеграция права; апроксимация права; рецепция права; адаптация права; globalization; universalisation of national law; means for universalization of law; internationalization of law; harmonization of law; law implementation; integration of Law; approximation of law; reception of law; adaptation of law